Developing intercultural communicative competence – the two sides of the coin - Svetlana Dimitrova-Gyuzeleva (Educational Role of Language Journal, 2020)
Effective intercultural communicative competence goes beyond a good command of the foreign language and an insight into the foreign culture. What real-life intercultural communication often calls for is an ability to present one’s own cultural identity in the foreign tongue. Are our learners empowered to face this challenge and how can the foreign language teacher cater for this need? The aim of this paper, which was developed on the basis of the author’s presentation at the 4th conference of the Educational Role of Language network “From theory to practice, from practice to theory”, is to outline the contemporary understanding of the essence of intercultural communicative competence underpinning the need for language teachers to devote equal attention to both the target and the local culture and language in order to prepare competent language users who can function as efficient mediators in the process of intercultural communication. In an answer to some of the deficiencies identified in educational practice, some practical ideas are also shared on how to exploit the rich affordance of language classes to enhance both the language command and the intercultural communicative competence of the learners.